APLIKASI LIMBAH CAIR BIOGAS DAN PUPUK NITROGEN PADA TANAMAN PAKCHOY (Brassica chinensis L.) - Lendri Irawan; Armaini '; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research was conducted at the experimental farm of the Agriculture Faculty, University of Riau started in April to June 2015. This study aims to look at the provision of bio-slurry, nitrogen fertilizer and interactionbetween the provision of bio-slurryandnitrogenfertilizerandto get thebestcombinationforgrowth and crop productionof pakchoy. Field experiment using a completely randomized factorial design, where 0, 2, 4, 6 liters/m2 of bio-slurry as the first factor and 0, 15, 25 g/m2of nitrogen fertilizer as the second factor. This study uses 12 combinations, 3 replications and 4 plant samples. Parameters measured were plant height, number of leaves, leaf area, weight of plants per plot, weight inveterate consumable plants and plant dry weight. Data results are then tested further variance with Duncan multiple test at 5%level. The results showed that the interaction of bio-slurry and nitrogen fertilizer treatment increased the plant height, number of leaves, leaf area, weight of plants per plot, plant fresh weight and dry weight consumable crops. Pakchoy production is highest in the treatment of 2 liters/m2 of bio-slurry and 15 grams/m2 ofnitrogen fertilizer. Keywords: bio-slurry, nitrogen fertilizer,pakchoy